2003
DOI: 10.1002/j.1551-8833.2003.tb10295.x
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing watershed pathogen research

Abstract: Water treatment professionals are generally aware of the issues regarding the fate and transport of pathogens within watersheds. However, not all water treatment professionals are in a scientific field nor do they all have the same level of knowledge of the range of international projects being conducted to address this issue. To counter a current lack of quantitative data on the biophysical and chemical parameters that drive pathogen survival and transport in watersheds, the authors created a conceptual model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Vegetated buffer strips (VBS) have been promoted as a way to reduce runoff pollution from agricultural land (19), but their effectiveness in removing bacteria has varied from study to study (9,16). This variation is believed to be due to the different soils, slopes, and flow rates used across experiments (1) and to differences in the degrees of bacterial attachment to particles (31).…”
mentioning
confidence: 99%
“…Vegetated buffer strips (VBS) have been promoted as a way to reduce runoff pollution from agricultural land (19), but their effectiveness in removing bacteria has varied from study to study (9,16). This variation is believed to be due to the different soils, slopes, and flow rates used across experiments (1) and to differences in the degrees of bacterial attachment to particles (31).…”
mentioning
confidence: 99%
“…There have been few attempts to quantify the relationship between pathogen dispersion and transport, rainfall, and surface water pathogen loads. Recent reviews (18,20) identified that artificial buffer strips can be highly effective at retarding oocyst transport (7), with vegetated setbacks as little as 1 m being considered sufficient in one watershed. Models to estimate sediment and nutrient export from land and design criteria to predict the retardation of these pollutants by buffer strips (41) are available.…”
mentioning
confidence: 99%
“…Oocysts present in animal fecal deposits on land are clearly responsible for many event-related increases in the concentrations of in-stream pathogens in watersheds (3,8). However, there are significant knowledge gaps regarding the mechanisms and magnitude of pathogen transport and the effects of environmental factors on oocyst inactivation (7). In particular, there have been few attempts to predict the fate of oocysts deposited on land by using quantifiable parameters.…”
mentioning
confidence: 99%